Growth of thin films of single-chain magnets on functionalized silicon surfaces. Issue 5 (4th March 2018) - Castellano, M.; Ferrando-Soria, J.; Moliner, N.; Cano, J.; Julve, M.; Lloret, F.
Abstract: A one-pot strategy for the direct growth of continuous and regular thin films of a neutral oxamato-bridged heterobimetallic chain, synthesized from Co 2+ nitrate and the tetramethylammonium salt of the anionic copper(II) complex (Me4 N)2 [Cu(2, 6-Et2 pa)2 ]·6H2 O (1 ) (2, 6-Etpa =  N -2, 6-diethylphenyloxamate) over Si(111) surfaces functionalized with carboxylic acid terminating groups has been developed. Variation of the growth conditions can provide important differences in the morphology of the obtained films when working in H2 O at 20 °C. An anisotropic growth of 1-D fibers is observed under stoichiometric conditions (Co 2+ /1  = 1:1), while an isotropic growth of 3-D particles occurs for an excess of Co 2+, as demonstrated by AFM. The dc magnetic measurements performed over the fiber- (3d ) or particle-based films (3e ) show a characteristic behavior of a 1-D ferrimagnetic chain compound. They are comparable to the ones of the bulk material of formula [CoCu(2, 6-Et2 pa)2 (H2 O)2 ] (2 ) prepared in H2 O at 20 °C which possesses slow magnetic relaxation effects typical of a SCM. Abstract :